Phosphoenolpyruvate carboxykinase in cell metabolism: Roles and mechanisms beyond gluconeogenesis - Shuo Yu; Simin Meng; Meixiang Xiang; Hong Ma (Molecular Metabolism, 2021)
Background: Phosphoenolpyruvate carboxykinase (PCK) has been almost exclusively recognized as a critical enzyme in gluconeogenesis, especially in the liver and kidney. Accumulating evidence has shown that the enhanced activity of PCK leads to increased glucose output and exacerbation of diabetes, whereas the defects of PCK result in lethal hypoglycemia. Genetic mutations or polymorphisms are reported to be related to the onset and progression of diabetes in humans. Scope of review: Recent studies revealed that the PCK pathway is more complex than just gluconeogenesis, depending on the health or disease condition. Dysregulation of PCK may contribute to the development of obesity, cardiac hypertrophy, stroke, and cancer. Moreover, a regulatory network with multiple layers, from epigenetic regulation, transcription regulation, to posttranscription regulation, precisely tunes the expression of PCK. Deciphering the molecular basis that regulates PCK may pave the way for developing practical strategies to treat metabolic dysfunction. Major conclusions: In this review, we summarize the metabolic and non-metabolic roles of the PCK enzyme in cells, especially beyond gluconeogenesis. We highlight the distinct functions of PCK isoforms (PCK1 and PCK2), depict a detailed network regulating PCK's expression, and discuss its clinical relevance. We also discuss the therapeutic potential targeting PCK and the future direction that is highly in need to better understand PCK-mediated signaling under diverse conditions.